2010
DOI: 10.1007/978-3-642-13486-9_27
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Repository Service for Vocabularies and Alignments in the Cultural Heritage Domain

Abstract: Abstract. Controlled vocabularies of various kinds (e.g., thesauri, classification schemes) play an integral part in making Cultural Heritage collections accessible. The various institutions participating in the Dutch CATCH programme maintain and make use of a rich and diverse set of vocabularies. This makes it hard to provide a uniform point of access to all collections at once. Our SKOS-based vocabulary and alignment repository aims at providing technology for managing the various vocabularies, and for explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The shift from printed books to digital tools for the management and use of controlled vocabularies already lead in the 1990s to a considerable body of research regarding automated and semi-automated methods for achieving interoperability between vocabularies (Doerr, 2001;Tudhope et al, 2011;van der Meij et al, 2010;van Erp et al, 2011). Isaac et al (2008) identified four general approaches towards vocabulary reconciliation or alignment: 1) lexical alignment techniques, 2) structural alignment, 3) extensional alignment, and 4) alignment using background knowledge.…”
Section: Linked Data and The Potential Of Entity Extraction For The Dmentioning
confidence: 99%
“…The shift from printed books to digital tools for the management and use of controlled vocabularies already lead in the 1990s to a considerable body of research regarding automated and semi-automated methods for achieving interoperability between vocabularies (Doerr, 2001;Tudhope et al, 2011;van der Meij et al, 2010;van Erp et al, 2011). Isaac et al (2008) identified four general approaches towards vocabulary reconciliation or alignment: 1) lexical alignment techniques, 2) structural alignment, 3) extensional alignment, and 4) alignment using background knowledge.…”
Section: Linked Data and The Potential Of Entity Extraction For The Dmentioning
confidence: 99%
“…For sharing and evaluating alignments, FOAM was relying on the Alignment API. Recently, [19] has taken inspiration from the Alignment API in order to share alignments between terminologies.…”
Section: Related Systemsmentioning
confidence: 99%
“…There are some methodological guidelines proposed for ontology matching [15], but those guidelines do not treat the ontology mapping process as a collaborative undertaking and only focuses on the creation and management of mappings; the guidelines do not take into account activities such as feasibility studies when the need for creating an ontology mapping arises. As for the state of the art, throughout sections 1 to 3 we have stated that most methods either do not take into account collaboration or focus only on a few of the activities (e.g., discovery and sharing [11]). Collaboration has been studied in, for instance, in [16] the focus was in circulating the correspondences between communities.…”
Section: Related Workmentioning
confidence: 99%
“…Another work done to find alignment and mappings between vocabularies cultural heritage collections through a web based repository service [11]. While designing the repository service, it was taking into consideration the need for vocabulary experts in the mapping activities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation